Impact of Ethical Leadership on Organizational Commitment and Organizational Citizenship Behavior with Mediating role of Intrinsic Motivation - Danish, Rizwan Qaisar; Hafeez, Shahid; Ali, Hafiz Fawad; Mehta, Ahmad Muneeb; Ahmad, Muhammad Bilal; Ali, Muhammad (International Review of Management and Marketing, 2020)
Ethical leadership in the field of organizational behavior and management has emerged as a significant area of interest in the recent leadership literature. There are, however, few studies that empirically examine the impact of ethical leadership through mediation processes on organizational engagement and citizenship actions. We have built a conceptual model to check whether ethical leadership effects the Organizational Citizenship Behaviour and commitment of organizational citizenship through the mediation of intrinsic motivation. For data collection, sample size of 340 was determined through item response theory. Data was collected through self-administrated questionnaire from different commercial banks located in geographical premises of Lahore, Pakistan. SPSS and AMOS software were used to carry out the analysis, structural equation modeling technique was applied to test the direct and indirect relationships. The results indicated that ethical leadership has a positive effect on the association of organizational commitment and citizenship behaviour within organizations. In fact, intrinsic motivation mediates between the relationship of ethical leadership and the conduct of organizational citizenship. Nevertheless, results also show that in the banking sector there is no mediating effect of intrinsic motivation between ethical leadership and organizational citizenship behaviour. Limitations have been discussed, as have future guidelines. Keywords: Ethical leadership, Organizational commitment, Organizational citizenship behavior, Intrinsic motivation, Banking sector, Pakistan JEL Classification: M19 DOI: https://doi.org/10.32479/irmm.9840